Robust industrial strains as platform for de novo resveratrol production from carbon sources: establishing grounds for an integrated process - Costa, Carlos E. (2019)
The search for robust microorganisms is essential to design sustainable and industrially attractive processes. Saccharomyces cerevisiae has a wide range of applications in the food industry, being also a valuable platform as a robust cell factory to yield several chemicals of interest, from biofuels to high-value natural products. Resveratrol is a polyphenolic antioxidant compound, generally extracted by a complex and lowefficiency process from the roots of Japanese knotweed, which makes it dependent on the supply of plant resources and environmental factors. Alternatively, it can also be synthesized chemically, but this method is also very complex and polluting. Considering this, its production through microbial biosynthesis can be a valuable alternative to side these drawbacks, nonetheless is generally achieved at the cost of expensive substrates as p-coumaric acid. de novo resveratrol production from glucose was recently reported in laboratory haploid yeast strains[1]. Stemmed on this knowledge, here, a set of robust industrial diploid strains was engineered using the CRISPR/Cas9 system and screened for its aptitude for resveratrol production. Initially, strains were engineered with Tyrosine ammonia lyase, which converts tyrosine to p-coumaric acid, in order to evaluate p-coumaric production, a key precursor in the resveratrol pathway. From here, pcoumaric- producing strains were selected and successfully engineered for de novo resveratrol production using glucose as sole carbon source, by overexpressing four plant genes, named resveratrol central pathway (RCP). The influence of the pentose phosphate pathway (PPP) on the de novo resveratrol production was then assessed. An alternative version of the top-producing strain, where four genes of the PPP were previously overexpressed, was used as platform for the integration of the RCP genes. The combination of these genes revealed a significant improvement in resveratrol titre. Altogether, this work establishes grounds for the development of an integrated biomass-to-resveratrol process in an industrial context.